SAE Technical Paper Series 2005
DOI: 10.4271/2005-01-3136
|View full text |Cite
|
Sign up to set email alerts
|

Particle Emissions from SI-Engines During Steady State and Transient Operating Conditions

Abstract: Particle emissions from four spark ignition engines were measured during steady state and transient chassis dynamometer tests. Transient Unified Drive Cycle tests were conducted at 0 °C and room temperature. Particle number, size distribution, active surface area, and photoelectric activity were determined. The results generally show low emission values for steady state operation of the warm engine. High particle concentrations are emitted in the first phase of the highspeed steady state testing. Once the engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Higher accumulation mode concentrations are consistent with higher mass emissions that were expected during a cold-cold start test. The hot start emissions were much lower and, based upon the CPC data, decreased from test to test (Kasper et al, 2004); this is reasonable since the engine and exhaust system would be warmer for each subsequent test.…”
Section: Chassis Dynamometer Experimentsmentioning
confidence: 96%
See 1 more Smart Citation
“…Higher accumulation mode concentrations are consistent with higher mass emissions that were expected during a cold-cold start test. The hot start emissions were much lower and, based upon the CPC data, decreased from test to test (Kasper et al, 2004); this is reasonable since the engine and exhaust system would be warmer for each subsequent test.…”
Section: Chassis Dynamometer Experimentsmentioning
confidence: 96%
“…Results from these instruments are reported elsewhere (Kasper et al, 2004). A variety of ambient and exhaust gas analyzers were also used throughout the project.…”
Section: Emissions Laboratory and Instrumentationmentioning
confidence: 99%
“…Various tests have already been carried out on vehicles with different types of engine. Generally, it is found that particles are generated during acceleration and cold start in a drive cycle. For port fuel injection gasoline vehicles, after catalyst light-off, particle emissions diminished to near negligible levels at moderate cruise speeds and during deceleration.…”
Section: Introductionmentioning
confidence: 99%
“…from gasoline engines are primarily in the 7-to 55-nm range during cold start (13). Now widely accepted, the low concentration of larger solid particles favors the formation of nuclei mode (diameter < 30 nm) particles (14) because of the small surface area available for gas-toparticle condensation. Also, many studies have focused more on diesel engines because they traditionally have had higher emissions rates, but diesel vehicles have lower cold-start emissions than gasoline vehicles (15,16).…”
mentioning
confidence: 99%